Salicylic acid receptors activate jasmonic acid signalling through a non-canonical pathway to promote effector-triggered immunity - Lijing Liu (Nature Portfolio, 2016)
Salicylic acid (SA) and jasmonic acid (JA) often act antagonistically in plant defence. Here, Liu et al. show that during effector-triggered immunity (ETI) against Pseudomonas syringae, JA signalling is activated via a non-canonical pathway involving the SA receptors, NPR3 and NPR4, to positively regulate ETI.